2015
DOI: 10.4103/0301-5742.165555
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of pharyngeal airway space and tongue position in individuals with different body types and facial patterns: A cephalometric study

Abstract: Human beings are normally nasal breathers. The nasal and the oral cavities serve as pathways for respiratory airflow, however in some individuals due to nasal airway inadequacy or habit; the oral cavity becomes the predominant route for the respiratory airflow. [1] Changes in the dimensions of the respiratory tract that is, constriction can cause a decrease in airflow at times. [2] There are significant relationships between the pharyngeal dimensions and craniofacial abnormalities. [3] Literature supports the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Works on the study of the relationship between the parameters of the soft palate and other structures of the human body are quite few in the scientific literature. Thus, Kulshrestha R. and co-authors [12] found significant differences for the value of the angle of inclination of the soft palate in groups with hypo-and hyperdivergent patterns of facial growth (p<0.003).…”
Section: Discussionmentioning
confidence: 89%
“…Works on the study of the relationship between the parameters of the soft palate and other structures of the human body are quite few in the scientific literature. Thus, Kulshrestha R. and co-authors [12] found significant differences for the value of the angle of inclination of the soft palate in groups with hypo-and hyperdivergent patterns of facial growth (p<0.003).…”
Section: Discussionmentioning
confidence: 89%
“…Little studies pay attention to the effect of changes in tongue position on the pharyngeal airway volume. (32,33) Despite that limited evidence was found between upper pharyngeal airway and head position (32) . On the other hand Ono et al 2000 (34) with the use of magnetic resonance image studied the effects of head positions on the volume of the pharyngeal airway and found that a significant increase in volume of the pharyngeal retro-glossal region when the patient rotated his head.…”
Section: Discussionmentioning
confidence: 99%